2018
DOI: 10.1103/physrevd.98.034031
|View full text |Cite
|
Sign up to set email alerts
|

Interface effects of strange quark matter with density dependent quark masses

Abstract: We study the interface effects in strangelets adopting mean-field approximation (MFA). Based on an equivparticle model, the linear confinement and leading-order perturbative interactions are included with density-dependent quark masses. By increasing the confinement strength, the surface tension and curvature term of strange quark matter (SQM) become larger, while the perturbative interaction does the opposite. For those parameters constrained according to the 2M strange star, the surface tension is ∼2.4 MeV/f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 98 publications
3
30
0
Order By: Relevance
“…Note that at μ B ≈ 1400 MeV, for few cases, the perturbation model predicts smaller baryon number density of quark matter than that of hadronic matter, which causes fluctuations if the surface tension is estimated with Σ ¼ 14.3Δn þ 1.3. At larger μ B , the relation 0.3Σ MRE ≈ 14.3Δn þ 1.3 can be fulfilled approximately, which coincides with the predictions of equivparticle model [62,63]. With the surface tension values indicated in Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Note that at μ B ≈ 1400 MeV, for few cases, the perturbation model predicts smaller baryon number density of quark matter than that of hadronic matter, which causes fluctuations if the surface tension is estimated with Σ ¼ 14.3Δn þ 1.3. At larger μ B , the relation 0.3Σ MRE ≈ 14.3Δn þ 1.3 can be fulfilled approximately, which coincides with the predictions of equivparticle model [62,63]. With the surface tension values indicated in Fig.…”
Section: Resultssupporting
confidence: 85%
“…The surface tension predicted by the MRE method is then obtained with Σ ¼ Σ MRE ¼ P i¼u;d;s Σ MRE i . Nevertheless, the MRE method tends to overestimate the surface tension by twice the value obtained with equivparticle model [62,63]. This is mainly due to the different confinement potential adopted in those models, where the bag mechanism of the MRE method introduces an infinite wall that results in a sharp density discontinuity.…”
Section: B the Quark-hadron Interfacementioning
confidence: 96%
See 2 more Smart Citations
“…It is found that σ c (in MeV/fm 2 ) increases linearly with µ T (in MeV) and can be well approximated with σ c = 0.23(µ T − 930) + 19, where the coefficients depend on the EoSs of HM and QM. In such cases, if the deconfinement phase transition occurs at large µ T , the emergence of geometrical structures may be inevitable in hybrid stars since typical estimations suggest σ < σ c with σ < ∼ 30 MeV/fm 2 [77][78][79][80][81][82][83][84]86].…”
Section: B Geometrical Structuresmentioning
confidence: 99%